Comparison between microdebrider assisted surgery and the conventional methods in the surgical treatment of nasal polyps - Bellad, Shama A.; Manjunath, N.; Ravi, Shilpa (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Microdebrider is emerging as a convenient tool for various ENT surgeries that helps in easier disease clearance and reduced morbidity. Though it requires some surgical expertise initially to master the skill of handling it, it is worth procuring and using in endoscopic sinus surgery. The present study was conducted to compare the microdebrider assisted endoscopic surgery and conventional methods using sinus endoscopes in the surgical management of nasal polyps. Methods: 30 patients diagnosed with nasal polyposis between the age group of 5 to 60 were equally randomized into 2 surgical groups- powered endoscopic sinus surgery group and conventional endoscopic sinus surgery group with 15 patients in each group. The study aimed at comparing the intra operative (blood loss, duration of surgery) and post operative results (crusting, scarring, discharge, symptoms, recurrence) between the two groups using Lund–Mackay scoring system and visual analogue scale. The data was statistically analysed. Results: A significant statistical evidence for a shorter operative time, dryness of the field, better surgical conditions and improved VAS scoring at 3 and 6 months postoperatively was observed in the powered endoscopy group than using conventional techniques. Conclusions: The use of microdebrider in endoscopic sinus surgery has the advantage of complete clearance of disease, smoother intra operative course and better post operative healing when compared to conventional instruments in the treatment of nasal polyps.